Relationship Between Body Image and Balanced Nutrition Knowledgewith Nutritional Status of Adolescent Girls - Sari Risnawati; Ana Nur Filiya; Nining Tyas Triatmaja; Denis Melati; Nuzul Dwi Utami (Ficco Scientific Corner, 2026)
Background: Adolescence is a critical period characterized by increased vulnerability to nutritional problems influenced by psychosocial and cognitive factors. This cross-sectional study aimed to analyze the relationship between body image and balanced nutrition knowledge with the nutritional status of adolescent girls at SMPN 4 Kediri. Methods: A total of 127 female students were selected using simple random sampling. Body image was assessed using the Multidimensional Body-Self Relations Questionnaire–Appearance Scales (MBSRQ-AS), balanced nutrition knowledge was measured using a structured questionnaire based on national guidelines, and nutritional status was determined using body mass index-for-age. Results: The results showed that most respondents were aged 14 years (73.2%), had normal body image (49.6%), good nutrition knowledge (89.9%), and normal nutritional status (72.4%). Bivariate analysis indicated a significant relationship between body image and nutritional status (p = 0.008) as well as between balanced nutrition knowledge and nutritional status (p < 0.001); however, multivariate analysis demonstrated no significant simultaneous association. Conclusion: These findings suggest that body image and nutrition knowledge are important individual factors related to adolescent nutritional status, highlighting the need for comprehensive and school-based nutrition education interventions.